Does more trade potential remain in Arab states of the Gulf? - Salim, Ruhul; Kabir, M.; Mawali, N. (Center for International Economics, Sejong Institution Sejong University, 2011)
This paper examines whether the Gulf Cooperation Council Countries (GCC) exerted any trade enhancing impact on its members by employing standard augmented gravity model as well as stochastic frontier gravity model. Panel data sets are constructed over the period of 1980 to 2008 for imports and exports of the bloc’s main trading partners along with GCC countries. The major finding is that the trade enhancing effect of the bloc is significant. However, there is still huge unutilized trade potential between the member countries. Several diagnostic tests were run to check and rectify possible problems of heteroskedasticity and autocorrelation as well as cross-sectional dependence.